Review of Controllable Risk Factors for the Development of Malignant Neoplasms of the Digestive Organs - N. K. Dauletnazarov; Y. E. Vyazovichenko; N. V. Torchinsky (Эпидемиология и вакцинопрофилактика, 2025)
Relevance. It is known that malignant neoplasms develop over a long period, under the constant influence of risk factors. Among them some biological agents, smoking and alcohol consumption are known to science. At the present stage the possibility of influence of such risk factors as sleep disorders, eating habits, obesity and overweight is being studied.Aim. To estimate, according to the literature data, the degree of influence of some controllable risk factors on the development of malignant neoplasms of the digestive organs.Materials and methods. The results of 130 articles conducted by Russian and foreign researchers were studied, from which 31 studies were selected that met the requirements of the selection criteria and corresponded to the objectives of the study. Based on the data presented in the studies, we analyzed relative risks, odds ratios and risk ratios of some controllable risk factors for the development of malignant neoplasms of the digestive organs.Results and Discussion. H. pylori, which contributes to the development of gastric cancer (OR 2.39 [95% CI 1.53–3.74]), stands out among the best-known cancer risk factors. Alcohol, a group 1 carcinogen (WHO), increases the risk (OR) of esophageal cancer by a factor of 2 [95% CI 1.66–2.40], liver cancer by a factor of 1.83 [95% CI 1.39–2.40] and gastric cancer by a factor of 1.54 [95% CI 1.10–2.15]. Smoking has been shown to cause more gastric cardia cancer (Hazard ratio/КШ 4.10 [95% CI: 1.76–9.57]) than distal gastric cancer (КШ 1.94 [95% CI: 1.05–3.60]). Most of the trials also focused on the effect of dietary habits on the development of cancer. For example, consumption of 100 g/day of red and processed meat was associated with the development of colorectal cancer (OR – 1.25, [95% CI: 1.10–1.43] and OR – 1.31, [95% CI: 1.13–1.52], respectively). Meanwhile, the researchers found an association between increased BMI and the risk of esophageal adenocarcinoma (OR, 1.10 [95% CI 1.04–1.17]). Sweet tea and fresh food consumption have also been shown to play a protective role against the development of gastrointestinal cancer (OR 0.26 [95% CI 0.14–0.47] and OR 0.57 [95% CI 0.37–0.88], respectively). In addition, the literature suggests a positive effect of sleep disorders and depression on the development of cancer.Conclusions. The presence of lifestyle risk factors such as the presence of H.pylori, consumption of fried and stale foods, daily consumption of red and processed meat of 100g or more has a significant impact on the development of digestive organ cancer. In addition, known WHO eradicable factors such as tobacco smoking and alcohol consumption have evidence of their influence on the development of digestive cancers. However, these risk factors require further in-depth study to develop systematic prevention measures. However, all the risk factors studied are manageable. If their influence is reduced or eliminated from human activity, the risk of developing digestive organ cancer is significantly reduced.